2013
DOI: 10.1093/hmg/ddt248
|View full text |Cite
|
Sign up to set email alerts
|

A systemic sclerosis and systemic lupus erythematosus pan-meta-GWAS reveals new shared susceptibility loci

Abstract: Systemic sclerosis (SSc) and systemic lupus erythematosus (SLE) are two archetypal systemic autoimmune diseases which have been shown to share multiple genetic susceptibility loci. In order to gain insight into the genetic basis of these diseases, we performed a pan-meta-analysis of two genome-wide association studies (GWASs) together with a replication stage including additional SSc and SLE cohorts. This increased the sample size to a total of 21,109 (6835 cases and 14,274 controls). We selected for replicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 42 publications
6
79
0
Order By: Relevance
“…Martin et al also described an association in the PXK locus, but this association was reported to be dependent on the SSc-related missense mutation in the DNASE1L3, rs35677470, in Mayes et al [18,136]. Finally, this report identified a novel locus for SSc that had already been reported to be associated with SLE, JAZF1 [136]. These studies confirm that, despite the clinical differences between these two systemic autoimmune disorders, the genetic susceptibility regions are greatly shared.…”
Section: Shared Risk Factors: Links With Other Autoimmune Diseasessupporting
confidence: 69%
See 2 more Smart Citations
“…Martin et al also described an association in the PXK locus, but this association was reported to be dependent on the SSc-related missense mutation in the DNASE1L3, rs35677470, in Mayes et al [18,136]. Finally, this report identified a novel locus for SSc that had already been reported to be associated with SLE, JAZF1 [136]. These studies confirm that, despite the clinical differences between these two systemic autoimmune disorders, the genetic susceptibility regions are greatly shared.…”
Section: Shared Risk Factors: Links With Other Autoimmune Diseasessupporting
confidence: 69%
“…Additionally, a recent meta-GWAS combining SSc and SLE patients has yielded a novel common locus, KIAA0319L, for both disorders [136]. Martin et al also described an association in the PXK locus, but this association was reported to be dependent on the SSc-related missense mutation in the DNASE1L3, rs35677470, in Mayes et al [18,136]. Finally, this report identified a novel locus for SSc that had already been reported to be associated with SLE, JAZF1 [136].…”
Section: Shared Risk Factors: Links With Other Autoimmune Diseasesmentioning
confidence: 69%
See 1 more Smart Citation
“…These studies have identified a substantial number of polymorphic loci associated with the risk of SSc. 7 The most prominent of these genetic associations are within the major histocompatibility complex (MHC). The great majority of the non-MHC variants associated with SSc are related to immune cell activation and function, including T and B cell signaling, along with innate immunity, type I interferon, and toll-like receptor (TLR) signaling.…”
Section: Tlr4-damp Signaling In Persistent Fibrosismentioning
confidence: 99%
“…They also revealed candidate causal non-HLA SNPs, genes, and pathways involved in RA (Lee et al, 2012). In order to reveal the genetic basis of systemic sclerosis (SSc) and SLE, Martin et al (2013) performed a panmeta-analysis of two GWAS together with a replication stage. This study identified KIAA0319L as a novel susceptibility locus for SSc and SLE, and they also determined that the previously described SLE susceptibility loci PXK and JAZF1 are shared with SSc.…”
mentioning
confidence: 99%